2017
DOI: 10.1038/tp.2017.152
|View full text |Cite
|
Sign up to set email alerts
|

Serum fatty acid patterns in patients with schizophrenia: a targeted metabonomics study

Abstract: Previous studies have indicated that schizophrenia is linked to abnormal lipid metabolism. Free fatty acids (FFAs) in peripheral blood can reflect the status of lipid metabolism in human body. The purpose of this study was to scan the FFA pattern and elucidate the characteristics of lipid metabolic abnormality in schizophrenia patients. One hundred and ten patients with schizophrenia (SCZs) and 109 healthy controls (HCs) were included in the study and divided into a discovery set and a validation set. Forty-se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(28 citation statements)
references
References 54 publications
4
22
0
2
Order By: Relevance
“…In fact, our team have revealed a phenomenon of elevated free fatty acids and ketone bodies in SZ patients’ serum in a metabolomic study 47 and later a validating lipidomic study. 48 We proposed for increased lipolysis in SZ patients and a transfer of energy substance to the brain for energy supply. Such an increased consumption of free fatty acids in SZ might additionally contribute to the reduced level of membrane fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, our team have revealed a phenomenon of elevated free fatty acids and ketone bodies in SZ patients’ serum in a metabolomic study 47 and later a validating lipidomic study. 48 We proposed for increased lipolysis in SZ patients and a transfer of energy substance to the brain for energy supply. Such an increased consumption of free fatty acids in SZ might additionally contribute to the reduced level of membrane fatty acids.…”
Section: Discussionmentioning
confidence: 99%
“…DHA and EPA are structurally integrated via phospholipid molecules and they ensure the proper structure of neuronal cell membranes [3]. FAs regulate the expression of genes, as well as changes in protein concentration, which could be blocked to some extent in SZ patients [36].…”
Section: Discussionmentioning
confidence: 99%
“…First, reduced total FFA levels may imply an increased regeneration of cell membranes and possible alterations in beta-oxidations of fatty acid metabolism at the early course of SZ. While plenty of studies have focused on the PUFA levels in SZ ( Van der Kemp et al, 2012 ), few have discussed other FAs and the total FA levels in SZ ( McEvoy et al, 2013 ; Yang et al, 2017 ). Recently, a decreased total plasma FFA levels was detected in FEANS patients with limited sample sizes ( Zhou et al, 2017 , 2018 ).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, previous studies showed that several fatty acid beta-oxidation enzymes were significantly increased in the brains of SZ patients, which implied enhanced beta-oxidation in FEANS patients ( Prabakaran et al, 2004 ). Up-regulated beta-oxidation in peripheral tissues of SZ patient has also been suggested by comparing product-to-precursor ratios of serum FFAs ( Yang et al, 2017 ). The decreased FFAs levels thus may result from a depleted source in membrane phospholipids as lipids metabolism was shifted toward beta-oxidation in the cytosol.…”
Section: Discussionmentioning
confidence: 99%